Historical Review of Blambangan in 1309 - 1763 - nurmaria, nurmaria; Rinda Handayani; Pitutur Tustho Gumawang (Islah: Journal of Islamic Literature and History, 2025)
Due to its geographical location at the eastern tip of Java Island, Blambangan was often contested by other kingdoms, considered strategic as it formed the border between Java and Bali. This study aims to examine the establishment and existence of Blambangan kingdom from a historical perspective. This study is based on two questions about whether Blambangan was an independent kingdom or part of another. The other kingdom referred to was either the Kingdom of Bali in the east or the Majapahit Empire in the west. The research method used was historical method, preceded by heuristic process, criticism, interpretation and historiography. Based on the research findings, Blambangan was founded in 1309 as part of the Majapahit Empire, given by Raden Jayanegara to Arya Wiraraja as a reward for his loyalty. This study discusses important events in history including the succession of kings over time, the separation of Blambangan into western and eastern regions, the transfer of the kingdom's capital, the expansion of the territory as part of the peak of the glory of the Blambangan Kingdom, and the death of King Danuningrat, which marked the end of Tawang Alun dynasty, from a historical perspective.